(2R*,3R*,4aS*,6aR*,11aS*,11bS*)-Methyl 2-acetoxy-11b-hydroxy-3,7-dimethyl-1,2,3,4,4a,5,6,6a,7,11,11a,11b-dodecahydrophenanthro[3,2-b]furan-3-carboxylate - Prathap, S. J. (International Union of Crystallography, 2007)
In the title compound, C(22)H(30)O(6), the conformation of the molecule is dictated by an intramolecular C—H⋯O contact. The crystal structure is stabilized via intermolecular C—H⋯O, O—H⋯O and C—H⋯π contacts.